Overview of the sterile insect technique for Aedes aegypti in Lee County, Florida, USA - Rachel Morreale; Steven Stenhouse; Johanna Bajonero; Danilo O. Carvalho; Nicole Foley; Roxanne Connelly; Aaron Lloyd; David Hoel (Infectious Diseases of Poverty)
Abstract Background Lee County Mosquito Control District (LCMCD) is an independent taxing district that works to protect human health and improve quality of life in Lee County, Florida, USA. With local dengue transmission in southern Florida, LCMCD prioritized the control of Aedes aegypti. Due to the cryptic larval habitats of Ae. aegypti and insecticide resistance, effective control using conventional methods is difficult. Thus, the sterile insect technique (SIT) program, using X-ray irradiated male mosquitoes, was created to target Ae. aegypti. The goal of this program was to suppress Ae. aegypti through establishing a robust SIT program and performing a pilot study in the field to assess the impacts of SIT releases. Main text The SIT program at LCMCD released sterile male Ae. aegypti from 2020 to 2022 in Captiva Island, Florida. The SIT program works within a larger Integrated Mosquito Management (IMM) framework and is not a standalone tool. The SIT program consists of nine employees, one of which is dedicated to quality assurance. Quality assurance assessments are performed routinely and periodically. Due to widespread destruction throughout Captiva and Sanibel Islands from Hurricane Ian in September 2022, the SIT pilot in Captiva Island was concluded and moved to Fort Myers, Florida. During the pilot study on Captiva Island, various lessons were learned and this knowledge has been applied to efforts in Fort Myers. Conclusions LCMCD has established a successful SIT program to suppress populations of Ae. aegypti. Through connections with the International Atomic Energy Agency (IAEA) and the University of Florida, LCMCD received guidance from experts in the field to help ensure the program’s success. Stable funding through taxes levied specifically for mosquito control provided essential consistency, allowing the program to grow and evolve. Consistent trapping routines provided immense amounts of entomological data. Thoughtful and intentional community engagement was essential in ensuring acceptance of the SIT program in Lee County. Following the phased conditional approach suggested by IAEA, LCMCD has built an effective and resilient SIT program. The integration of the SIT as a tool of an area-wide mosquito control program is a feature that distinguishes LCMCD’s SIT program from others.